Water Governance: effective needs for Sustainable Development - Mukesh Kumar Mishra (ZBW - Leibniz Information Centre for Economics, 2023)
Over the past decades, there has been increasing competition for the available water resources and increasing water pollution. Consequently, water shortages, water quality degradation, and destruction of the aquatic ecosystem are seriously affecting prospects for economic and social development, political stability, as well as ecosystem integrity. In developing countries, scarcity and degradation of water resources may have a severely limiting impact on development options, especially for poor people. In order to meet basic human and ecological needs and services, societies need to address and solve several serious water challenges and must come to terms with dwindling water resources, their uneven geographic and seasonal distribution, and an inadequate and inequitable allocation of water services. Poor resource management, corruption, inappropriate institutional arrangements, bureaucratic inertia, insufficient human capacity, and shortages of finances for investments also undermine the effective governance of water in many places. These are also the challenges to be addressed by governance reforms. There is general agreement that improvements to water governance are a necessary part of the solution to the specific challenges that fall within this nexus of water ecosystem management and poverty reduction within the context of climate change. The objective of this paper is to contribute to integrated, participatory governance processes and a sense of urgency around the need to reclaim and rejuvenate water bodies in more effective ways to ensure the sustainable and equitable use of water resources and to expand the delivery of clean water supply and sanitation services to all, which will help the effort of the impact under "Jal-Jeevan-Hariyali Abhiyan."
Keywords: Q25; Q2; 330; Water Governance; Integrated water management